Analyzing the Elements of X-ray Emission Spectrum of C/1999 S4 (LINEAR) and 9p/ Tempel 1 Comets - Hanash, Ruaa Faraj; Khalaf, Salman Zaidan; Abood, Khaleel I. (Iraqi Journal of Science, 2024)
The study focused on the elemental abundance of two different comets. These comets were observed at an energy range of (100-10000) eV. The X-ray emission spectrum was analyzed and the results showed that comet C/1999 S4 (LINEAR) from the Oort cloud region (long-period) and comet 9p/Tempel 1 from the Kuiper Belt region (short-period) had the highest abundances of the different elements. The ds9 program used data from NASA’s Chandra analysis to show the spectra of these comets and analyze their elements. The results showed that some elements were similar in all comets, such as (Carbon (C), Oxygen (O), Neon (Ne), and Silicon (Si)). While others varied from one comet to another, such as (Magnesium (Mg) and Chlorine (Cl)) elements which appeared in the C/1999 S4 (LINEAR) comet, and (Aluminum (A) and Phosphors (P)) elements which appeared in the 9P/Tempel 1 comet. This is due to these comets’ areas of presence, where the elements of comets can be classified through their areas of presence.